Attitude and Perception of Farmers Towards e-Learning - Renu Balakrishnan , Monika Wason , R. N. Padaria , Premlata Singh and Eldho Varghese, (Indian Journal of Extension Education, 2013)
e-Learning is a new concept to our agricultural system,where most of the farming communities have low access to theright information sources. It can contribute a lot through the provision of apt learning situation to officials, agriculturestudents as well as farmers and will dramatically improve agricultural education by allowing greater access toinformation. The study was undertaken in the Malappuram district of Kerala state to determine the attitude and perceptionof farmers towards e-learning. A group of sixty e-learners and sixty non e-learners was selected randomly to obtainsignificant information. It was found out that although the benefits of e-learning are many like easy access to information,time and cost effective, flexible; even then non e- learners had a negative attitude and unfavorable perception indextowards e- learning.